A New Method to Evidence the P300 Event-related Potential based on a Lifting Scheme - Radu, U.; Lazar, A. -M.; Istrate, M. (Elektronika ir Elektrotechnika, 2013)
We explore the possibility of revealing the P300 event-related potential by means of a dedicated method that is both fast and reliable. It involves a lifting scheme based on a variant of Haar non-linear wavelet and a decision criterion based on a measure computed after the information linked with the P300 potential were obtained from the EEG signal. Some actual results are presented, for comparison purposes, involving the signals given in a well known database of EEG recordings. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.2348